UKOA D366 dissolved methane (CH4) and nitrous oxide (N2O) concentrations from CTD bottle samples. - Brown, Ian; Rees, Andrew (British Oceanographic Data Centre, Natural Environment Research Council, 2014)
Concentrations of dissolved nitrous oxide (N2O) and methane (CH4) were determined in seawater samples collected from CTD casts during cruise D366 onboard RRS Discovery between 7th June and 5th July 2011. Investigations were undertaken during the UK-Ocean Acidification cruise during June 6th to July 12th 2011, which departed from and returned to Liverpool, UK. A total of 75 CTD casts were undertaken at stations in the NW European shelf sea, from which 34 were sampled for CH4 and N2O concentration profiles and a further 5 were used for Ocean Acidification bioassay experiments. The cruise was the first of three cruises which contributed to the NERC funded UK Ocean Acidification Research Programme.